COLLABORATIVE GOVERNANCE IN FLOOD MANAGEMENT IN PEKANBARU CITY - Jesika Silalahi; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
One of the ways the Pekanbaru City government handles flooding is by carrying out River Normalization, the management of which collaborates with various parties, but the collaboration carried out by both parties has not yet had a significant impact. For this reason, an analysis of collaboration in managing flood management in Pekanbaru City is needed. This research aims to find out how Collaborative Governance is implemented in flood management in Pekanbaru City and find out the obstacles to implementing Collaborative Governance in flood management in Pekanbaru City. This research uses the Ansell and Gash theory with the indicators used, namely, Initial Conditions, Institutional Design, Facilitative Leadership, and Collaboration Process. The results of this research show that there has been collaboration for flood management in Pekanbaru City. The implementation of collaboration can be said to be quite good or quite effective, but not yet optimal, this is proven because there are still several indicators that are not optimal. On the other hand, the coordination carried out still has weaknesses, namely that there is still no clear agreement between several agencies, so there are no binding regulations and sanctions.